2018
DOI: 10.1039/c8dt03833c
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the spin state and geometry in tricobalt paddlewheel complexes with halide axial ligands

Abstract: A series of tricobalt EMACs with halide axial ligands demonstrate diverse spin-crossover behaviors as a function of the molecular geometry and the nature of the axial ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This is a surprisingly rare example of a structurally characterised Co( iii ) fluorido complex, with only four reported in the CSD. 45–48 In this case, the Co( iii ) ion sits 0.054 Å out of the equatorial mean plane defined by the four N donor atoms, and a hydrogen-bonding interaction between the fluorido ligand and a water molecule ( d F⋯O = 2.712 Å) is present. The nitrito-κ 1 O complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is a surprisingly rare example of a structurally characterised Co( iii ) fluorido complex, with only four reported in the CSD. 45–48 In this case, the Co( iii ) ion sits 0.054 Å out of the equatorial mean plane defined by the four N donor atoms, and a hydrogen-bonding interaction between the fluorido ligand and a water molecule ( d F⋯O = 2.712 Å) is present. The nitrito-κ 1 O complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For both type of metal‐strings, i. e., those in which the metal ions are linearly placed via coordination to multidentate ligands and those in which preformed links are connected by covalent or non‐covalent unsupported metal‐metal bonds, the influence of the capping ligands placed at the end of the chains on the structural, electronic, photo‐physical, and magnetic properties is remarkable. For example, in the case of the most studied trinuclear EMACs, featuring [X−{M 3 }−X] cores, it has been demonstrated that the identity of these ligands (X) significantly affects the metal⋅⋅⋅metal separations, the antiferromagnetic coupling parameter, [32] and the luminescence [33] (M=Ni), the symmetrical (Cr−Cr−Cr) versus unsymmetrical (Cr≡Cr⋅⋅⋅Cr) structures, [34] the spin‐crossover properties (M=Co), [35] the color in mixed‐valent trinuclear platinum chains, [36] as well as the metal–metal bond order and electric conductance (M=Ru) [37] . Moreover, the spin‐state of Co [7c] and Ni [8a] ions in [X−Cr 2 Co−X] and [Ni 3 (NCS) 2/1 ] 0/+1 systems, respectively, can be tuned by the π‐donor/acceptor properties of the axial ligands.…”
Section: Introductionmentioning
confidence: 99%